The Influence of Service Quality And Profit Sharing on Customers' Saving Decisions Bank Syariah Indonesia (BSI) KCP Batam Batu Aji - Tipani Anisah; Sunargo Sunargo (Komunitas Dosen Indonesia, 2024)
This study aims to determine the effect of Service quality and profit sharing on saving decision at Bank Syariah Indonesia (BSI) KCP Batam Batu Aji. This study uses a quantitative approach, with a sample of 197 respondents. Data collection techniques in this study are by using a questionnaire distribution. The analysis techniques used in this study includes validity test, reliability test, multiple regression test, F test, t test and coefficient of determination. The data that has fulfilled the analysis techniques was processed using the help of the SPSS 26 program. It can be seen from the results of the statistical test that the service quality and profit sharing independent variables affect the dependent variable of saving decision. The results showed that based on the calculation of the coefficient of determination the influence of the independent variable service quality and profit sharing on the dependent variable of saving decision is 0,532 or 53.2 % which shows that saving decision can be influenced by service quality variable and profit sharing variable. While the remaining 46.8 % is influenced by other variables that do not exist in this study. This shows that service quality and profit sharinghas a significant effect on saving decision. Where if service quality is guaranteed and profit sharing is good will improve saving decision.